A concise guide for student writers - Glorfeld, Louis E (Holt, Rinehart and Winston, 1963)
This brief textbook has three purpose: to show college freshmen how to plan and begin a theme; to help them overcome those writing faults the experience has shown to be most frequest in freshman composition; to teach them the standard methods of developing thought in paragraphs and the devices that will enable them to achieve a smooth, readable style.